COVID-19 in China: A Rapid Review of the Impacts on the Mental Health of Undergraduate Students - Hairong Shi; Haixue Zhu; Yan Ni (Frontiers Media S.A., 2022)
Public health crises pose challenges for governments and health systems, and the coronavirus disease 2019 (COVID-19) has presented major challenges to humans worldwide. In the context of COVID-19 in China, we explore the impacts of the pandemic on the mental health of undergraduate students. We examine pandemic prevention and control measures in Chinese universities through a rapid review and use our findings to explain the difficulties that undergraduate students face. Moreover, our analysis examines the impacts on five aspects of mental health: emotional aspects, personality, interpersonal relationships, learning behavior and employment options. Additionally, we provide implications in four areas based on the application of the study: strengthening psychological intervention, promoting government information disclosure, improving family communication and adjusting self-awareness.